2014
DOI: 10.1088/0004-637x/790/2/111
|View full text |Cite
|
Sign up to set email alerts
|

Charge State Evolution in the Solar Wind. Iii. Model Comparison With Observations

Abstract: We test three theoretical models of the fast solar wind with a set of remote sensing observations and in-situ measurements taken during the minimum of solar cycle 23. First, the model electron density and temperature are compared to SOHO/SUMER spectroscopic measurements. Second, the model electron density, temperature, and wind speed are used to predict the charge state evolution of the wind plasma from the source regions to the freeze-in point. Frozen-in charge states are compared with Ulysses/SWICS measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 56 publications
1
30
0
Order By: Relevance
“…It is possible to do this with a variety of models including different Poynting flux values or magnetic field geometries (open or closed) in different regions such as coronal holes, and even eruptions constituting transients in the solar wind (e.g., Lynch et al, 2011;Gruesbeck et al, 2011;Landi et al, 2012aLandi et al, ,b, 2014Lepri et al, 2012;Oran et al, 2015;Rodkin et al, 2016).…”
Section: Non-equilibrium Ionization and Solar Windmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible to do this with a variety of models including different Poynting flux values or magnetic field geometries (open or closed) in different regions such as coronal holes, and even eruptions constituting transients in the solar wind (e.g., Lynch et al, 2011;Gruesbeck et al, 2011;Landi et al, 2012aLandi et al, ,b, 2014Lepri et al, 2012;Oran et al, 2015;Rodkin et al, 2016).…”
Section: Non-equilibrium Ionization and Solar Windmentioning
confidence: 99%
“…Evolution of charge state along an open magnetic field line was studied in a series of papers by Landi et al (2012aLandi et al ( ,b, 2014. It was found that windinduced departures from ionization equilibrium existed in the solar atmosphere, producing up to a factor of 3 differences in total radiative losses of the upper chromosphere and transition region when compared to equilibrium ion composition (Landi et al, 2012b).…”
Section: Non-equilibrium Ionization and Solar Windmentioning
confidence: 99%
“…(left) Cranmer et al [] coronal hole/fast wind model. (right) Empirical model with the wind source region located in the corona (from Landi et al []).…”
Section: Visible Plasma Diagnostic Techniquesmentioning
confidence: 99%
“…One of the leading proposed mechanisms for heating the solar corona (and accelerating the solar wind) is dissipation of magnetic waves. This method powers many first-principle, physics-based global coronal models, such as the Alfvén Wave Solar Model [van der Holst et al, 2014]. There are many mechanisms proposed for how to dissipate magnetic waves and release their energy into the solar atmosphere, but all require observational evidence.…”
Section: Coronal Heating By Magnetic Wavesmentioning
confidence: 99%
See 1 more Smart Citation